Chemical mechanical polishing solution and application

By optimizing the components and content of the chemical mechanical polishing liquid, one-step molding and polishing of GaSb single wafer is achieved, which solves the problems of active chemical properties of the GaSb single wafer surface and complex polishing process, and obtains high-quality surfaces and shortened polishing time.

CN119912878AActive Publication Date: 2025-05-02XINYUEMICRO ELECTRONIC MATERIALS (JIAXING) CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510408435.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-02
Publication Date
2025-05-02
Estimated Expiration
2045-04-02

AI Technical Summary

Technical Problem

The surface of GaSb single wafer has active chemical properties and is easily oxidized, resulting in difficult chemical effects. The existing polishing process is complex and costly, making it difficult to achieve high-quality surfaces.

Method used

A chemical mechanical polishing liquid is provided, including abrasive particles, polishing promoters, oxidants, surfactants, pH adjusters and water, and one-step molding and polishing of GaSb single wafers is achieved by optimizing components and content.

Benefits of technology

High-quality surface polishing of GaSb single wafers is achieved, with low roughness and no scratches, orange peel, matte surface and other defects, and the polishing time is shortened from more than 2 hours to about 15 minutes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a chemical mechanical polishing solution and application thereof. The chemical mechanical polishing solution comprises grinding particles, a polishing accelerant, an oxidizing agent, a surfactant, a pH regulator and water. The polishing accelerant comprises inorganic acid salt of alkali metal and organic acid salt of alkali metal; the inorganic acid salt of the alkali metal comprises one or more of carbonate of the alkali metal, bicarbonate of the alkali metal, nitrate of the alkali metal and sulfate of the alkali metal; the organic acid salt of the alkali metal comprises one or more of oxalate of the alkali metal, acetate of the alkali metal, citrate of the alkali metal, phthalate of the alkali metal and diamine tetraacetate of the alkali metal. According to the method, one-step forming of polishing of the GaSb single crystal wafer is achieved, the process is simple, stability is good, the time needed by original polishing is shortened to about 15 minutes from 2 hours or above, the surface of the GaSb single crystal wafer is smooth and clean, defects such as scratches, orange peels and matte faces do not exist, and the roughness Ra can reach 0.3 nm or below.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of semiconductors, and in particular relates to a chemical mechanical polishing liquid and an application thereof. Background Art

[0002] III-V semiconductors are compound semiconductor materials formed by the combination of III-group elements and V-group elements. Commonly used III-group elements are mainly boron, aluminum, gallium, and indium, and commonly used V-group elements are mainly nitrogen, phosphorus, arsenic, and antimony. Gallium antimonide (GaSb) is similar to indium phosphide (InP) and gallium arsenide (GaAs), and is a typical III-V compound semiconductor material with a cubic sphalerite structure. Compared with GaAs and InP, the surface of GaSb wafers is chemically active and easily oxidized. An oxide layer of several nanometers can be quickly formed on the surface in the air. The passivation effect of antimony oxide and its limited solubility make the chemical reaction of GaSb quite difficult.

[0003] In recent years, infrared detectors developed with epitaxial antimonide type II superlattice materials using GaSb as substrate material have shown excellent detection performance in the long-wave and very long-wave infrared bands, and have good application prospects in the fields of gas monitoring, night vision, infrared imaging, etc. The epitaxial growth of high-quality antimonide type II superlattice materials places high quality requirements on GaSb substrate materials. The substrate material needs to have low defect density, high lattice integrity, and an atomic-level flat epitaxial buffer layer, which places high demands on the surface quality of the GaSb substrate, and its application depends on the development of polishing technology. GaSb wafers have low hardness, brittle texture, and are prone to scratches, so it is necessary to conduct in-depth research to solve its processing technology problems.

[0004] In order to obtain a high-quality GaSb material surface, CN116652700A provides a manual polishing method for a GaSb single crystal wafer, and the wafer roughness Ra can reach below 0.70 nm, but manual polishing is difficult to standardize and is heavily dependent on human factors; CN106064326B discloses a polishing method for a GaSb single crystal wafer, and after polishing, the surface of the GaSb single crystal wafer is less damaged and easy to clean, and the surface roughness is less than 0.30 nm, but the entire polishing process is divided into rough polishing, medium polishing and fine polishing, and the polishing cloth, polishing liquid and polishing parameters used are all different, the process is complicated, and the use cost is high. Summary of the invention

[0005] The object of the present invention is to provide a chemical mechanical polishing liquid and its application. The chemical mechanical polishing liquid of the present invention can enable a GaSb single crystal wafer to obtain a high-quality surface with low roughness in only one step of polishing.

[0006] The present invention provides a chemical mechanical polishing liquid, comprising abrasive particles, a polishing accelerator, an oxidant, a surfactant, a pH regulator and water;

[0007] The polishing accelerator includes an inorganic acid salt of an alkali metal and an organic acid salt of an alkali metal;

[0008] The inorganic acid salt of the alkali metal includes one or more of alkali metal carbonates, alkali metal bicarbonates, alkali metal nitrates and alkali metal sulfates;

[0009] The alkali metal organic acid salt includes one or more of alkali metal oxalates, alkali metal acetates, alkali metal citrates, alkali metal phthalates and alkali metal diamine tetraacetates;

[0010] In the chemical mechanical polishing liquid, the mass ratio of the inorganic acid salt of the alkali metal to the organic acid salt of the alkali metal is (0.2 wt%~2 wt%): (0.05 wt%~0.5 wt%).

[0011] Preferably, the abrasive particles include one or more of aluminum oxide, ceria, silicon dioxide, titanium dioxide and zirconium oxide;

[0012] And / or, the average particle size of the abrasive particles is 10 to 1000 nm;

[0013] and / or, the inorganic acid salt of the alkali metal comprises one or more nitrates of the alkali metal;

[0014] And / or, the organic acid salt of the alkali metal includes one or more of C2-C6 alkylene or cycloalkylene diamine tetraacetate;

[0015] and / or, the oxidant comprises one or more of bromate, bromite, chlorate, chlorite, hydrogen peroxide, hypochlorite, iodate, monoperoxysulfate, monoperoxysulfite, monoperoxyphosphate, monoperoxyhypodyphosphate, monoperoxypyrophosphate, organic-halogen-oxygen compound, periodate, permanganate, peracetic acid and iron salt;

[0016] And / or, the surfactant includes one or more of anionic surfactants and nonionic surfactants;

[0017] And / or, the pH regulator includes one or both of an acid regulator and an alkali regulator;

[0018] And / or, the pH value of the chemical mechanical polishing solution is 9.2-10.2.

[0019] Preferably, the abrasive particles include one or more of colloidal silica, pyrogenic silica, precipitated silica and condensation-polymerized silica;

[0020] And / or, the average particle size of the abrasive particles is 50-500 nm;

[0021] And / or, the inorganic acid salt of the alkali metal includes one or both of potassium nitrate and sodium nitrate;

[0022] And / or, the organic acid salt of the alkali metal includes one or more of trans-1,2-cyclohexanediaminetetraacetate and ethylenediaminetetraacetate;

[0023] And / or, the oxidant is a peroxide, and the peroxide includes one or more of hydrogen peroxide, monopersulfate, monopersulfite, monoperphosphate, monoperoxydiphosphate, monoperoxypyrophosphate, and peracetic acid;

[0024] and / or, the surfactant comprises one or more of ethoxypropoxylated fatty alcohols, alkoxylated branched fatty alcohols, linear secondary alcohol polyoxyethylene ethers, polyethylene glycol stearates, fatty alcohol polyoxyethylene ether sodium sulfates, sarcosinates and taurates, dodecylbenzenesulfonic acid, alkyl carboxylic acid isomeric polyol amines, and acetylene glycol ethoxylates;

[0025] And / or, the pH regulator is an acid regulator, and the acid regulator includes one or more of hydrochloric acid, sulfuric acid, phosphoric acid, nitric acid, formic acid, acetic acid and oxalic acid;

[0026] And / or, the pH regulator is an alkali regulator, and the alkali regulator includes one or more of sodium hydroxide, potassium hydroxide, ammonium hydroxide, ethylenediamine and phenylethylamine.

[0027] Preferably, the polishing liquid further comprises an additive, wherein the additive comprises one or more of a buffer, a biocide, an antiscalant, a defoamer and a dispersant.

[0028] Preferably, in terms of mass percentage, the mass percentage of the abrasive particles in the polishing liquid is 0.1 wt% to 30 wt%;

[0029] And / or, the mass percentage of the inorganic acid salt of the alkali metal in the polishing liquid is 0.2 wt%~2wt%;

[0030] and / or, the mass percentage of the organic acid salt of the alkali metal in the polishing liquid is 0.05 wt% to 0.5 wt%;

[0031] And / or, the mass percentage of the oxidant in the polishing liquid is 0.01 wt%~8wt%;

[0032] And / or, the mass percentage of the surfactant in the polishing liquid is 0.001 wt%~1wt%.

[0033] Preferably, in terms of mass percentage, the mass percentage of the abrasive particles in the polishing liquid is 0.2 wt% to 25 wt%;

[0034] And / or, the mass percentage of the inorganic acid salt of the alkali metal in the polishing liquid is 0.2 wt%~1.5wt%;

[0035] And / or, the mass percentage of the organic acid salt of the alkali metal in the polishing liquid is 0.05 wt% to 0.4 wt%;

[0036] And / or, the mass percentage of the oxidant in the polishing liquid is 0.02 wt%~5wt%;

[0037] And / or, the mass percentage of the surfactant in the polishing liquid is 0.01 wt%~0.5wt%.

[0038] Preferably, the polishing liquid comprises silicon dioxide abrasive particles, potassium nitrate, trans-1,2-cyclohexanediaminetetraacetate, hydrogen peroxide, a surfactant, a pH regulator and water; the surfactant is a linear secondary alcohol polyoxyethylene ether and / or polyethylene glycol stearate.

[0039] The present invention provides the use of the chemical mechanical polishing liquid as described above in polishing a GaSb single wafer.

[0040] Preferably, the GaSb single wafer polishing comprises the following steps:

[0041] A) chemical mechanical polishing is performed on a GaSb single crystal wafer using a polishing cloth and the chemical mechanical polishing solution;

[0042] B) Cleaning the polished GaSb single crystal wafer.

[0043] Preferably, in step A), the GaSb single crystal is polished by a polishing machine, the polishing speed is 20 rpm to 70 rpm, and the polishing pressure is 300 g / cm 2 ~800 g / cm 2 The dripping rate of the chemical mechanical polishing liquid is 10 mL / min to 50 mL / min, and the polishing time is 5 min to 15 min;

[0044] And / or, the polishing cloth in step A) is made of polyurethane;

[0045] And / or, in the step B), the GaSb single crystal wafer is rinsed with deionized water and then scrubbed with ethanol, then sprayed with deionized water, and finally dried with nitrogen.

[0046] The present invention provides a chemical mechanical polishing liquid, comprising abrasive particles, a polishing accelerator, an oxidant, a surfactant, a pH regulator and water; the polishing accelerator comprises an inorganic acid salt of an alkali metal and an organic acid salt of an alkali metal; the inorganic acid salt of an alkali metal comprises one or more of an alkali metal carbonate, an alkali metal bicarbonate, an alkali metal nitrate and an alkali metal sulfate; the organic acid salt of an alkali metal comprises one or more of an alkali metal oxalate, an alkali metal acetate, an alkali metal citrate, an alkali metal phthalate and an alkali metal diamine tetraacetate; in the chemical mechanical polishing liquid, the mass ratio of the inorganic acid salt of an alkali metal to the organic acid salt of an alkali metal is (0.2 wt%~2wt%): (0.05 wt%~0.5wt%). The present invention realizes one-step forming of polishing of GaSb single crystal wafers by optimizing the components and content of the polishing liquid, without the need for three-step polishing of rough polishing, medium polishing and fine polishing, with a simple process and good stability, and shortens the time originally required for polishing from more than 2 hours to about 15 minutes. The GaSb single crystal wafer obtained by the polishing method described in the above technical solution has a high-quality surface and a smooth surface without defects such as scratches, orange peel, and matte, and the roughness Ra can reach below 0.3nm. DETAILED DESCRIPTION

[0047] The present invention provides a chemical mechanical polishing liquid, comprising abrasive particles, a polishing accelerator, an oxidant, a surfactant, a pH regulator and water;

[0048] The polishing accelerator includes an inorganic acid salt of an alkali metal and an organic acid salt of an alkali metal;

[0049] The inorganic acid salt of the alkali metal includes one or more of alkali metal carbonates, alkali metal bicarbonates, alkali metal nitrates and alkali metal sulfates;

[0050] The organic acid salt of the alkali metal includes one or more of alkali metal oxalates, alkali metal acetates, alkali metal citrates, alkali metal phthalates and alkali metal alkyldiaminetetraacetates;

[0051] In the chemical mechanical polishing liquid, the mass ratio of the inorganic acid salt of the alkali metal to the organic acid salt of the alkali metal is (0.2 wt%~2 wt%): (0.05 wt%~0.5 wt%).

[0052] In the present invention, the chemical mechanical polishing liquid can achieve excellent polishing effect for GaSb wafers with high polishing difficulty and shorten the total polishing time. It is also applicable to the chemical mechanical polishing treatment of compound semiconductor materials formed by the combination of group III elements and group V elements, such as GaAs, InP, GaSb, InAs, InSb, InAsSb, InGaAs, AlGaSb, InAlSb, AlGaAsSb, GaInAsSb, etc., but not vice versa. Considering the higher polishing difficulty of GaSb wafers during polishing, it is difficult for polishing liquids suitable for other semiconductor materials to achieve the technical effect of the polishing liquid in the present invention.

[0053] In the present invention, the abrasive particles preferably include one or more of aluminum oxide, ceria, silicon dioxide, titanium dioxide and zirconium oxide, more preferably silicon dioxide, and the silicon dioxide may be any suitable form of silicon dioxide, such as one or more of colloidal silicon dioxide, pyrogenic silicon dioxide, precipitated silicon dioxide and polycondensed silicon dioxide; the average particle size of the abrasive particles is preferably 10 to 1000 nm, more preferably 50 to 500 nm, further preferably 70 to 300 nm, specifically, such as 10 nm, 30 nm, 50 nm, 70 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, preferably a range value with any of the above values ​​as the upper or lower limit.

[0054] In the present invention, the abrasive particles are suspended in the polishing liquid, and the mass percentage of the abrasive particles in the chemical mechanical polishing liquid is preferably 0.1%~30%, more preferably 0.2%~25%, such as 0.1%, 0.2%, 0.5%, 1%, 5%, 10%, 15%, 20%, 25%, 30%, preferably a range value with any of the above values ​​as the upper or lower limit.

[0055] In the present invention, the polishing accelerator can chemically react with the polished material or combine with one of the components of the polished material to form a substance with weaker binding force or bond to increase the removal rate of the polished material; the polishing accelerator preferably includes an inorganic acid salt of an alkali metal and an organic acid salt of an alkali metal.

[0056] In the present invention, the inorganic acid salt of the alkali metal includes one or more of alkali metal carbonates, alkali metal bicarbonates, alkali metal nitrates and alkali metal sulfates; the alkali metal in the inorganic acid salt of the alkali metal is preferably one or more of lithium, sodium and potassium; specifically, in an embodiment of the present invention, the inorganic acid salt of the alkali metal may be one or more of potassium nitrate, potassium sulfate and potassium carbonate, and the mass percentage of the inorganic acid salt of the alkali metal in the chemical mechanical polishing liquid is preferably 0.2%~2%, more preferably 0.2%~1.5%, more preferably 0.5%~1.5%, such as 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, preferably a range value with any of the above values ​​as the upper or lower limit.

[0057] In the present invention, the alkali metal organic acid salt includes one or more of alkali metal oxalates, alkali metal acetates, alkali metal citrates, alkali metal phthalates and alkali metal diamine tetraacetates, and more preferably includes one or more of C2-C6 alkylene or cycloalkylene diamine tetraacetates, such as ethylenediamine tetraacetate and / or 1,2-cyclohexanediamine tetraacetate; the alkali metal in the alkali metal organic acid salt is preferably one or more of lithium, sodium and potassium; specifically, in an embodiment of the present invention, the alkali metal organic acid salt is It can be one or more of sodium citrate, disodium ethylenediaminetetraacetate and 1,2-cyclohexanediaminetetraacetate; the mass percentage of the organic acid salt of the alkali metal in the chemical mechanical polishing liquid is preferably 0.05%~0.5%, more preferably 0.05%~0.4%, more preferably 0.1%~0.4%, such as 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, preferably a range value with any of the above values ​​as the upper or lower limit.

[0058] In the present invention, the oxidant preferably includes one or more of bromate, bromite, chlorate, chlorite, hydrogen peroxide, hypochlorite, iodate, monoperoxysulfate, monoperoxysulfite, monoperoxyphosphate, monoperoxydiphosphate, monoperoxypyrophosphate, organic-halogen-oxygen compound, periodate, permanganate, peracetic acid and iron salt (such as ferric nitrate); the mass percentage of the oxidant in the chemical mechanical polishing liquid is preferably 0.01% to 8%, more preferably 0.02% to 5%, such as 0.01%, 0.02%, 0.05%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 6%, 7%, 8%, preferably a range value with any of the above values ​​as the upper or lower limit.

[0059] In the present invention, the surfactant is preferably an anionic surfactant and / or a nonionic surfactant, such as ethoxylated propoxylated fatty alcohols, alkoxylated branched fatty alcohols, linear secondary alcohol polyoxyethylene ethers, polyethylene glycol stearates, fatty alcohol polyoxyethylene ether sodium sulfates, sarcosinates and taurates, dodecylbenzenesulfonic acid, alkyl carboxylic acid isomeric polyol amines and acetylene glycol ethoxylates. One or more of the following; the mass percentage of the surfactant in the chemical mechanical polishing liquid is preferably 0.001% to 1%, more preferably The amount of the aqueous phase is selected to be 0.01% to 0.5%, such as 0.001%, 0.005%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, preferably a range value with any of the above values ​​as the upper or lower limit.

[0060] In the present invention, the pH regulator preferably includes an acid regulator and / or an alkali regulator, the acid regulator is one or more of hydrochloric acid, sulfuric acid, phosphoric acid, nitric acid, formic acid, acetic acid and oxalic acid, and the alkali regulator is one or more of sodium hydroxide, potassium hydroxide, ammonium hydroxide, ethylenediamine and phenylethylamine; the pH value of the chemical mechanical polishing liquid is preferably 9.2~10.2.

[0061] According to actual needs, the chemical mechanical polishing liquid in the present invention may also include other additives, such as one or more of a buffer, a biocide, an antiscalant, a defoamer, and a dispersant.

[0062] The present invention does not impose any particular limitation on the preparation method of the chemical mechanical polishing liquid, which can be obtained by mixing the abrasive particles, polishing accelerator, oxidant, surfactant, pH adjuster and water mentioned above in a conventional mixing manner, wherein the oxidant may decompose in the presence of some additives. In this case, the oxidant can be added before use.

[0063] The present invention also provides an application of the chemical mechanical polishing liquid described above in polishing a GaSb single wafer, wherein the GaSb single wafer polishing comprises the following steps:

[0064] A) chemical mechanical polishing of a GaSb single wafer is performed using the chemical mechanical polishing solution described above;

[0065] B) Cleaning the polished GaSb single crystal wafer.

[0066] The present invention preferably uses a polishing cloth in combination with the chemical mechanical polishing solution described above to perform chemical mechanical polishing on the GaSb single crystal wafer, and before chemical mechanical polishing, the GaSb single crystal wafer to be polished is placed on a wax-free adsorption pad soaked in water and fixed.

[0067] In the present invention, the polishing cloth is preferably a polishing cloth made of polyurethane material, more preferably a polishing cloth made of black polyurethane material, the rotation speed of the chemical mechanical polishing is preferably 20-70 rpm, more preferably 30-60 rpm, such as 20 rpm, 30 rpm, 40 rpm, 50 rpm, 60 rpm, 70 rpm, preferably a range value with any of the above values ​​as the upper or lower limit; the pressure of the chemical mechanical polishing is preferably 300-800 g / cm 2 , more preferably 400-700 g / cm 2 , such as 300 g / cm 2 , 400 g / cm 2 , 500 g / cm 2 , 600 g / cm 2 , 700 g / cm 2 , 800 g / cm 2 , preferably a range value with any of the above numerical values ​​as the upper or lower limit; during the chemical mechanical polishing process, the dripping rate of the chemical mechanical polishing liquid is preferably 10-50 mL / min, more preferably 20-40 mL / min, such as 10 mL / min, 15 mL / min, 20 mL / min, 25 mL / min, 30 mL / min, 35 mL / min, 40 mL / min, 45 mL / min, 50 mL / min, preferably a range value with any of the above numerical values ​​as the upper or lower limit; the time of the chemical mechanical polishing varies according to the removal amount. Usually, the removal amount is 5-20 μm, and the time of the chemical mechanical polishing is 5min-15min, more preferably 8min-12min, such as 5 min, 6 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, preferably a range value with any of the above numerical values ​​as the upper or lower limit.

[0068] After the chemical mechanical polishing is completed, the present invention sequentially rinses the polished GaSb single crystal wafer with deionized water and scrubs it with ethanol, then sprays it with deionized water and blows it dry with nitrogen to obtain the polished GaSb single crystal wafer.

[0069] The present invention provides a chemical mechanical polishing liquid, comprising abrasive particles, a polishing accelerator, an oxidant, a surfactant, a pH regulator and water; the polishing accelerator comprises an inorganic acid salt of an alkali metal and an organic acid salt of an alkali metal; the inorganic acid salt of an alkali metal comprises one or more of an alkali metal carbonate, an alkali metal bicarbonate, an alkali metal nitrate and an alkali metal sulfate; the organic acid salt of an alkali metal comprises one or more of an alkali metal oxalate, an alkali metal acetate, an alkali metal citrate, an alkali metal phthalate and an alkali metal alkyl diamine tetraacetate; in the chemical mechanical polishing liquid, the mass ratio of the inorganic acid salt of an alkali metal to the organic acid salt of an alkali metal is (0.2 wt%~2wt%): (0.05 wt%~0.5wt%). The present invention realizes one-step forming of polishing of GaSb single crystal wafers by selecting and optimizing the components and contents of the polishing liquid, without the need for three-step polishing of rough polishing, medium polishing and fine polishing, with a simple process and good stability, and shortens the time originally required for polishing from more than 2 hours to about 15 minutes. The GaSb single crystal wafer obtained by the polishing method described in the above technical solution has a high-quality surface and a smooth surface without defects such as scratches, orange peel, and matte, and the roughness Ra can reach below 0.3nm.

[0070] In order to further illustrate the present invention, a chemical mechanical polishing liquid and application provided by the present invention are described in detail below in conjunction with embodiments, but it should not be understood as limiting the protection scope of the present invention.

[0071] Example 1 Effect of pH on GaSb Single Wafer Polishing

[0072] Polishing solutions with different pH values ​​were used to chemically mechanically polish GaSb single crystals (see Experimental Examples 1A, 1B, and 1C in Table 1). In addition to using potassium hydroxide solution to adjust the pH to 9.1, 10.2, and 11.2, respectively, the polishing solutions used in all experimental examples contained 20% colloidal silica, 1% potassium nitrate, 0.2% potassium trans-1,2-cyclohexanediaminetetraacetate, and 3% hydrogen peroxide, with the remainder being deionized water. A black non-grooved polyurethane polishing pad was used for polishing, with a polishing speed of 50 rpm, a downward pressure of 25 N, and a polishing liquid flow rate of 20 ml / min. The GaSb single crystal was placed in a wax-free adsorption pad soaked in deionized water and placed on a single-sided polishing machine for polishing for 5 minutes. After polishing, the GaSb single wafer was removed immediately and rinsed with deionized water overflow, then wiped with ethanol and dried with nitrogen. The mass change before and after polishing was compared using an electronic analytical balance with an accuracy of 0.0001g. The removal rate of the GaSb single wafer was calculated based on the mass change. The roughness of the GaSb single wafer was obtained using an atomic force microscope (scanning range of 5x5μm). The experimental results are shown in Table 1:

[0073] Table 1: GaSb removal rate and roughness

[0074]

[0075] From the data in Table 1, it can be seen that as the pH increases, the roughness tends to gradually increase. A higher removal rate and lower roughness can be achieved at a pH of 9.2. When the pH rises to 10.2, the removal rate decreases by about 15%. When the pH continues to rise to 11.2, the removal rate decreases further. This shows that for the chemical mechanical polishing of GaSb, the higher the pH, the lower the removal rate. In order to further verify this hypothesis, the pH was lowered to 8.2, and it was found that the aggregation of the polishing liquid particles caused poor stability of the entire system. Therefore, the optimal polishing pH range of this system is 9.2-10.2.

[0076] Example 2 Effect of Oxidant Concentration on Polishing of GaSb Single Wafer

[0077] Polishing solutions with different oxidant concentrations were used to chemically mechanically polish GaSb single crystals (Experimental Examples 2A, 2B, 2C, and 2D). In addition to containing different concentrations of hydrogen peroxide, the polishing solutions used in all experimental examples contained 20% colloidal silica, 1% potassium nitrate, and 0.2% potassium trans-1,2-cyclohexanediaminetetraacetate. Potassium hydroxide was used to adjust the pH to 10.2, and the rest was deionized water. The polishing parameters and the cleaning method of the GaSb single crystal were the same as those in Example 1. An electronic analytical balance with an accuracy of 0.0001g was used to weigh and compare the mass change before and after polishing. The removal rate of the GaSb single crystal was calculated by the mass change. The experimental results are shown in Table 2:

[0078] Table 2 GaSb removal rate

[0079]

[0080] From the data in Table 2, it can be seen that when the hydrogen peroxide concentration increases from 2% to 3%, the removal rate increases slightly. When the hydrogen peroxide concentration increases to 5%, the removal rate decreases by 50%. When the hydrogen peroxide concentration continues to increase to 7%, the removal rate increases slightly but cannot reach the level when the hydrogen peroxide concentration is 3%. In addition, with the increase of hydrogen peroxide concentration, the roughness experiences a trend of first decreasing and then increasing, and the roughness reaches the lowest at a concentration of 3%, indicating that a higher GaSb removal rate and lower roughness can be achieved at a hydrogen peroxide concentration of 3%.

[0081] Example 3 Effect of polishing accelerator on polishing of GaSb single wafer

[0082] Polishing liquids containing different types of promoters were used to chemically mechanically polish GaSb single crystals (Experimental Examples 3A, 3B, 3C, 3D, 3E, and 3F). The polishing liquids used in Experimental Examples 3A-3E all contained 20% colloidal silica, 1% potassium nitrate, and 3% hydrogen peroxide. Potassium hydroxide was used to adjust the pH to 9.2. Except for 3E, which did not contain organic acid salts, Experimental Examples 3A-3D and 3G all contained 0.2% of different types of organic acid salts, and the rest was deionized water. In addition, Experimental Examples 3E-3G are used to illustrate the synergistic promotion effect of potassium nitrate and organic acid salts. The polishing parameters and the cleaning method of the GaSb single crystal are the same as those in Example 1. An electronic analytical balance with an accuracy of 0.0001g was used to weigh and compare the mass changes before and after polishing. The removal rate of the GaSb single crystal was calculated by the mass change. The roughness of the GaSb single crystal was obtained by atomic force microscopy (scanning range was 5x5μm). The experimental results are shown in Table 3:

[0083] Table 3 GaSb removal rate and roughness

[0084]

[0085] Analyzing Table 3, it can be seen from 3A-3D that different types of organic acid salts and potassium nitrate can affect the GaSb removal rate and surface roughness to different degrees. Compared with Experimental Example 3F, Experimental Example 3E added 1% potassium nitrate alone, and the roughness was reduced while the removal rate was also increased (Rate 0.89μm / min, 71.15% increase relative to 3E), but the improvement of potassium nitrate on surface roughness and GaSb removal rate is limited. Preferably, the amount of potassium nitrate added does not exceed 2%. Further increasing the potassium nitrate content will affect the stability of the polishing liquid. Compared with Experimental Example 3F, Experimental Example 3G added 0.2% trans-1,2-cyclohexanediaminetetraacetic acid potassium alone, and the GaSb removal rate was significantly improved (Rate 1.27μm / min, 144.23% increase relative to 3E). Compared with Experimental Example 3F, Experimental Example 3D simultaneously added 1% potassium nitrate and 0.2% trans-1,2-cyclohexanediaminetetraacetic acid potassium, and the GaSb removal rate was significantly improved (Rate 4.95μm / min, an increase of 851.92% relative to 3E), and the effect was far greater than the addition of 1% potassium nitrate or 0.2% trans-1,2-cyclohexanediaminetetraacetic acid potassium alone, indicating that the two have a synergistic effect on improving the GaSb removal rate.

[0086] In summary, both inorganic acid salts and organic acid salts can accelerate the removal rate of GaSb to varying degrees. When the polishing liquid contains both, the removal rate of GaSb increases significantly, indicating that the two have a synergistic effect.

[0087] Example 4 Effect of surfactant on polishing of GaSb single wafer.

[0088] The same concentration but different types of surfactants were used to polish GaSb single crystal wafers (Experimental Examples 4A-4I). The polishing liquid used in all experimental examples contained 20% colloidal silicon dioxide, 1% potassium nitrate, 0.2% potassium trans-1,2-cyclohexanediaminetetraacetate, 3% hydrogen peroxide, and the rest was deionized water. Experimental Example 4J as a comparative example did not contain any surfactant. The other experimental examples contained 0.2% of different types of surfactants. The polishing parameters and the cleaning method of the GaSb single crystal wafer were the same as those in Example 1. An electronic analytical balance with an accuracy of 0.0001g was used to weigh and compare the mass change before and after polishing. The removal rate of the GaSb single crystal wafer was calculated by the mass change. The roughness of the GaSb single crystal wafer was obtained by atomic force microscopy (scanning range was 5x5μm). The experimental results are shown in Table 4:

[0089] Table 4 GaSb removal rate and roughness

[0090]

[0091] From the data in Table 4, it can be seen that different types of surfactants have different degrees of influence on the removal rate and roughness of GaSb single crystals. The roughness of experimental example 4C / 4D is good (Ra≤0.5nm). At the same time, the removal rate is reduced but still meets the requirements of the one-step GaSb polishing process. The one-step forming of GaSb single crystal polishing is realized without the need for three steps of rough polishing, medium polishing and fine polishing. The process is simple and has good stability, and the original polishing time is shortened from more than 2 hours to about 15 minutes. The surface of the polished wafer of experimental example 4C / 4D is observed under strong light. The surface is smooth and has no matte surface, scratches or residual particles.

[0092] Example 5 Synergistic Effects Between Polishing Accelerators

[0093] Example 3 verifies that in the absence of a surfactant, two polishing accelerators, inorganic acid salt and organic acid salt, have a synergistic effect on improving the GaSb removal rate. This example explores the effects of the two on the GaSb polishing rate when a surfactant is added.

[0094] Polishing accelerators of different concentrations and types were used to polish GaSb single wafers (Experimental Examples 5A-5F). The polishing liquid used in all experimental examples contained 20% colloidal silica, 0.2% linear secondary alcohol polyoxyethylene ether, and 3% hydrogen peroxide. Experimental Example 5G, as a comparative example, did not contain alkali metal inorganic salts. The remaining experimental examples contained alkali metal inorganic salts and / or trans-1,2-cyclohexanediaminetetraacetic acid potassium of different concentrations and types. The polishing parameters and the cleaning method of the GaSb single wafer were the same as those in Example 1. An electronic analytical balance with an accuracy of 0.0001 g was used to weigh and compare the mass change before and after polishing. The removal rate of the GaSb single wafer was calculated by the mass change. The roughness of the GaSb single wafer was obtained by atomic force microscopy (scanning range was 5x5μm). The experimental results are shown in Table 4:

[0095] Table 5 GaSb removal rate and roughness

[0096]

[0097] Analyzing the data in Table 5, the polishing accelerator of Experimental Example 5F is 1.2% potassium nitrate, the removal rate of GaSb is 0.44μm / min, and the roughness is >2nm. The polishing accelerator of Experimental Example 5G is 0.5% trans-1,2-cyclohexanediaminetetraacetic acid potassium, the removal rate of GaSb is 0.32μm / min, and the roughness is >2nm. Further increase in the content of organic acid salts does not further increase the removal rate of GaSb, but affects the stability of the polishing liquid. Therefore, the addition amount of organic acid salts is preferably not more than 0.5%. The polishing accelerator of Experimental Example 5B is 1% potassium nitrate and 0.2% trans-1,2-cyclohexanediaminetetraacetic acid potassium, the removal rate of GaSb is 0.78μm / min, and the roughness is 0.2nm. While the roughness is significantly reduced, the removal rate of GaSb is significantly improved, which is significantly better than 5F and 5G, indicating that there is a synergistic effect between organic acid salts and inorganic acid salts.

[0098] The different removal rates and roughness of Experimental Examples 5B, 5D, and 5E indicate that the synergistic effects of different types of inorganic acid salts and the same organic acid salts are not the same. While the removal rate of Experimental Example 5B is higher, a lower roughness can be achieved. The surface of the wafer after polishing in Experimental Example 5B is observed under strong light. The surface is smooth and has no matte surface, scratches, or residual particles. The polished GaSb in Experimental Examples 5D and 5E is difficult to clean, and there are more particles remaining on the surface, so the roughness is higher.

[0099] The results of Experimental Examples 5A-5C show that different potassium nitrate concentrations have a significant effect on the removal rate and roughness of GaSb. As the potassium nitrate concentration increases, the removal rate of GaSb gradually increases. However, compared with Experimental Example 5B, the roughness of GaSb after polishing in Experimental Example 5C is higher, and the polishing liquid is in poor condition, which is prone to stratification. Therefore, the content of potassium nitrate should not be greater than 2wt%.

[0100] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A chemical mechanical polishing liquid comprising abrasive particles, a polishing accelerator, an oxidant, a surfactant, a pH regulator and water; The polishing accelerator includes an inorganic acid salt of an alkali metal and an organic acid salt of an alkali metal; The inorganic acid salt of the alkali metal includes one or more of alkali metal carbonates, alkali metal bicarbonates, alkali metal nitrates and alkali metal sulfates; The alkali metal organic acid salt includes one or more of alkali metal oxalates, alkali metal acetates, alkali metal citrates, alkali metal phthalates and alkali metal diamine tetraacetates; In the chemical mechanical polishing liquid, the mass ratio of the inorganic acid salt of the alkali metal to the organic acid salt of the alkali metal is (0.2 wt%~2wt%):(0.05 wt%~0.5wt%).

2. The chemical mechanical polishing solution according to claim 1, characterized in that: The abrasive particles include one or more of aluminum oxide, ceria, silicon dioxide, titanium dioxide and zirconium oxide; And / or, the average particle size of the abrasive particles is 10 to 1000 nm; and / or, the inorganic acid salt of the alkali metal comprises one or more nitrates of the alkali metal; And / or, the organic acid salt of the alkali metal includes one or more of C2-C6 alkylene or cycloalkylene diamine tetraacetate; and / or, the oxidant comprises one or more of bromate, bromite, chlorate, chlorite, hydrogen peroxide, hypochlorite, iodate, monoperoxysulfate, monoperoxysulfite, monoperoxyphosphate, monoperoxyhypodyphosphate, monoperoxypyrophosphate, organic-halogen-oxygen compound, periodate, permanganate, peracetic acid and iron salt; And / or, the surfactant includes one or more of anionic surfactants and nonionic surfactants; And / or, the pH regulator includes one or both of an acid regulator and an alkali regulator; And / or, the pH value of the chemical mechanical polishing solution is 9.2-10.

2.

3. The chemical mechanical polishing solution according to claim 1, characterized in that: The abrasive particles include one or more of colloidal silica, pyrogenic silica, precipitated silica and condensation-polymerized silica; And / or, the average particle size of the abrasive particles is 50-500 nm; And / or, the inorganic acid salt of the alkali metal includes one or both of potassium nitrate and sodium nitrate; And / or, the organic acid salt of the alkali metal includes one or more of trans-1,2-cyclohexanediaminetetraacetate and ethylenediaminetetraacetate; And / or, the oxidant is a peroxide, and the peroxide includes one or more of hydrogen peroxide, monopersulfate, monopersulfite, monoperphosphate, monoperoxydiphosphate, monoperoxypyrophosphate, and peracetic acid; and / or, the surfactant comprises one or more of ethoxypropoxylated fatty alcohols, alkoxylated branched fatty alcohols, linear secondary alcohol polyoxyethylene ethers, polyethylene glycol stearates, fatty alcohol polyoxyethylene ether sodium sulfates, sarcosinates and taurates, dodecylbenzenesulfonic acid, alkyl carboxylic acid isomeric polyol amines, and acetylene glycol ethoxylates; And / or, the pH regulator is an acid regulator, and the acid regulator includes one or more of hydrochloric acid, sulfuric acid, phosphoric acid, nitric acid, formic acid, acetic acid and oxalic acid; And / or, the pH regulator is an alkali regulator, and the alkali regulator includes one or more of sodium hydroxide, potassium hydroxide, ammonium hydroxide, ethylenediamine and phenylethylamine.

4. The chemical mechanical polishing solution according to claim 1, characterized in that: The polishing liquid further includes additives, which include one or more of a buffer, a biocide, an antiscalant, a defoamer, and a dispersant.

5. The chemical mechanical polishing solution according to claim 1, characterized in that: In terms of mass percentage, the mass percentage of the abrasive particles in the polishing liquid is 0.1 wt% to 30wt%; And / or, the mass percentage of the inorganic acid salt of the alkali metal in the polishing liquid is 0.2 wt%~2wt%; and / or, the mass percentage of the organic acid salt of the alkali metal in the polishing liquid is 0.05 wt% to 0.5 wt%; And / or, the mass percentage of the oxidant in the polishing liquid is 0.01 wt%~8wt%; And / or, the mass percentage of the surfactant in the polishing liquid is 0.001 wt%~1wt%.

6. The chemical mechanical polishing solution according to claim 1, characterized in that: In terms of mass percentage, the mass percentage of the abrasive particles in the polishing liquid is 0.2 wt% to 25 wt%; And / or, the mass percentage of the inorganic acid salt of the alkali metal in the polishing liquid is 0.2 wt%~1.5wt%; And / or, the mass percentage of the organic acid salt of the alkali metal in the polishing liquid is 0.05 wt% to 0.4 wt%; And / or, the mass percentage of the oxidant in the polishing liquid is 0.02 wt%~5wt%; And / or, the mass percentage of the surfactant in the polishing liquid is 0.01 wt%~0.5wt%.

7. The chemical mechanical polishing solution according to claim 1, characterized in that: The polishing liquid comprises silicon dioxide abrasive particles, potassium nitrate, trans-1,2-cyclohexanediaminetetraacetate, hydrogen peroxide, a surfactant, a pH regulator and water; the surfactant is a linear secondary alcohol polyoxyethylene ether and / or polyethylene glycol stearate.

8. Use of the chemical mechanical polishing liquid as claimed in any one of claims 1 to 7 in polishing a GaSb single wafer.

9. The use according to claim 8, characterized in that: The GaSb single wafer polishing comprises the following steps: A) chemical mechanical polishing is performed on a GaSb single crystal wafer using a polishing cloth and the chemical mechanical polishing solution; B) Cleaning the polished GaSb single crystal wafer.

10. The use according to claim 9, characterized in that: In the step A), the GaSb single crystal is polished by a polishing machine, the polishing speed is 20 rpm to 70 rpm, and the polishing pressure is 300 g / cm 2 ~800 g / cm 2 The dripping rate of the chemical mechanical polishing liquid is 10 mL / min to 50 mL / min, and the polishing time is 5 min to 15 min; And / or, the polishing cloth in step A) is made of polyurethane; And / or, in the step B), the GaSb single crystal wafer is rinsed with deionized water and then scrubbed with ethanol, then sprayed with deionized water, and finally dried with nitrogen.

Citation Information

Patent Citations

  • A polishing method for gallium antimonide single wafers

    CN106064326B

  • Composition and method for polishing a sapphire surface

    CN101511532A

  • Chemical-mechanical planarization sizing agent

    CN102443351A

  • Chemical-mechanical polishing aqueous composition and use thereof

    CN103194148A

  • Chemical Mechanical Polishing (CMP) of Cobalt-Containing substrate

    CN107523219A